Conditions for high production of penicillin acylase and their effects on viability of its producer, escherichia coli - Nongluksna Sriubolmas (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Penicillin G acylase (PGA) from Escherichia coli is commonly used to catalyze hydrolysis of the amide bond in a penicillin molecule producing 6-aminopenicillanic acid, the key intermediate for synthesis of semisynthetic penicillins, and a corresponding side chain acid. Because of the high industrial value of PGA, plasmid pQEAl1, a high copy number plasmid containing pga gene under the control of tac promoter and lacI(q) previously constructed was used in this study. Studies on growth conditions for obtaining the maximum level of enzyme production have not been done. Moreover, it was found that the recombinant E. coli cells grew poorly under the IPTG induced condition. By varying growth temperatures, aeration (shaking velocities) and concentrations of IPTG, it was found that the optimum growth condition for E. coli DH5α pQEAll to produce maximum level of PGA was to grow the organism in L broth containing chloramphenicol (15 µg/ml) at 20 degree C, 120 rpm and with 0.1 mM IPTG induction for 72 h. The specific activity (U/mg of protein) of PGA produced under this condition was about 44 times higher than that produced under the uninduced condition. It was found that high production of PGA increased permeability of the outer membrane of cells as detected by increase in sensitivity to SDS and this resulted in leakage of the enzyme into the surrounding medium. SDS-PAGE and immunoblotting analyses of whole proteins of cells grown under various conditions indicated that post-translational processing was a common limiting step of the PGA synthesis under high temperature, high aeration and/or high IPTG concentration. Cells grown at these conditions produced low amount of PGA but accumulated high amount of the PGA precursor polypeptide. Transmission electron micrographs (TEM) of cells grown under 0.1 mM IPTG induction at temperatures of 20 and 25 degree C or grown under high IPTG concentrations at 25 degree C showed the presence of periplasmic inclusion bodies (IB) and/or cytoplasmic IB. Characterization of these isolated IB by immunoblotting analysis indicated that the periplasmic IB and the cytoplasmic IB were the PGA proenzyme (the precursor polypeptide lacking the signal peptide) and preproenzyme (the precursor pohypeptide containing the signal peptide), respectively. Results of this study suggested that accumulation of high amount of the precursor polypeptides led to IB formation which seem to be a possible cause of the deleterious effect of PGA overproduction. It also led to cell death as shown by Gram staining and also led to selection of mutants which are Pga(-) phenotype. The observation of cytoplasmic IB of the PGA preproenzyme suggested that translocation of PGA through cell membrane was a post-translational process. From the study with plasmid pDEAll, a deleted pQEAll plasmid which lacked some nucleotide sequences of the β-subunit region on the pga gene, showed that the deleted precursor polypeptide was produced but not processed. Accumulation of the deleted precursor protein to form IB, mainly of the cytoplasmic type, was seen. These indicated that the intact β-subunit was not only necessary for enzyme processing but also for translocation of the precursor polypeptide into the periplasm. Growth of E. coli DH5α pDEAll cells under induced condition at temperatures of 20-37 degree C caused a large numbers of cell death resulting in observation of the growth curves with very long lag periods compared to that of the uninduced cells. This was similar to that with E. coli DH5α pQEAl1 grown under induced condition at 37 degree C. This suggessted that overproduction of the deleted precursor protein and subsequently formation of IB led to cell death. This supported that aggregation of the precursor polypeptide was a possible cause of the detrimental effect of PGA overproduction leading to growth retardation and cell death as earlier proposed.